FIGURE 1 in Species circumscription of the Caltha leptosepala polyploid complex (Ranunculaceae) based on molecular and morphological data - Wefferling, Keir M.; Hoot, Sara B. (Zenodo, 2017)
FIGURE 1. Holotype of Caltha biflora, collected by A. Menzies, 1792. "Northwest coast of America, inland behind Banks Island." (between Haida Gwaii and mainland British Columbia, Canada). Housed at The Natural History Museum, London, England (BM565604). Inset photo shows a single narrow, filiform filament; magnified 5×. Published as part of Wefferling, Keir M. & Hoot, Sara B., 2017, Species circumscription of the Caltha leptosepala polyploid complex (Ranunculaceae) based on molecular and morphological data, pp. 201-223 in Phytotaxa 316 (3) on page 206, DOI:10.11646/phytotaxa.316.3.1, http://zenodo.org/record/13699892